(untitled) - USA, AMERICAN RADIO RELAY LEAGUE (USA, 1987)
1.Amateur radio / 2.Electrical fundamentals / 3.Radio design technique and lenguage / 4.Vacum tube principles / 5.Power Supplies / 6.Audio and video / 7.Digital Basics / 8.modulation an demodulation / 9.Radio - Frequency ocilators and synthesizers / 10.Radio trasnmitting principles / 11.Radio receiving principles / 12.Radio transceivers / 13.Repeaters / 14.RF power amplifiers / 15. Trasmission lines / 16 .Modulation methods / 17.Voice communications /18.Digital communications / 19.Image communications /20.Special modulation techniques /21.Transmission / 22.Radio frequencies and propagation /23.Space Communications / 24.Construction techniques /25.Test Equipment and measurements /26.Troubleshooting and repair/ 27.Power supply projects / 28.Audio and video Equipment /29.Digital Equipment /30.HF radio equipment / 31.VHF equipment / 32.UHF equipment /33.Antenna projects /34.Station accesories /35.Componet data / 36.How to become a radio amateur /37.Assembling a station / 38.Operating a station /39. Monitoring and direction finding /40.Interferce
Incluye indice analitico
Keywords: ELECTRONICA